Cloud-Based Mobile Monitoring of Mechanic Work Performance and Reporting in Oil Palm Plantation Workshops - Mutiara Cahyani; Ritna Wahyuni; Raden Aris Sugianto (Academic Bright Collaboration, 2026)
Purpose – Work reporting and mechanic activity monitoring in oil palm plantation workshops are still largely performed manually, resulting in delays in information delivery, recording errors, and difficulties in tracking work histories. This study aimed to develop a mobile application to support mechanical performance monitoring in a more structured and documented manner. Methods – This study employed the Extreme Programming (XP) methodology, which consists of the Planning, Design, Coding, and Testing phases. Data were collected through observations, interviews with the Workshop Assistant, and a literature review. The application was developed using C#, .NET MAUI, and a cloud database for centralized data management. Findings – The developed application integrates daily work reporting, activity documentation, work history management, user management, and report downloading into a single platform accessible to administrators and mechanics. Black Box Testing showed that all tested functions operated according to predefined requirements. Research Implications – The findings demonstrate the potential of mobile and cloud-based information systems to support the digitalization of reporting processes and operational information management in oil palm plantation workshops. However, the evaluation was limited to functional testing within a single workshop environment and did not include usability, user acceptance, or long-term operational impact assessments. Originality – This study presents a mobile application specifically designed for oil palm plantation workshops by integrating mechanic performance monitoring, work reporting, activity documentation, work history management, and cloud-based data management within a single platform.